SECTORAL ALLOCATION OF PUBLIC EXPENDITURE AND ITS EFFECT ON HARYANA’S ECONOMIC DEVELOPMENT - Deswal, Deepak; Bisht, Padam S; Mukta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the impact of sectoral allocation of public expenditure on Haryana's economic growth from 2000 to 2023. Using time series analysis, the research investigates the dynamic relationships between sectoral expenditures—specifically on education, health, agriculture, industry, and infrastructure—and the state’s Net State Domestic Product (NSDP). Stationarity tests reveal that most expenditure categories exhibit long-term stability, while some require differencing to achieve stationarity. Granger causality tests indicate significant short-term relationships for sectors like infrastructure and industry, while cointegration analysis confirms a robust long-term equilibrium between sectoral expenditures and economic growth. Regression results highlight that infrastructure and industry have the most substantial positive influence on NSDP, whereas education and health show a delayed impact. The findings reveal the importance of strategic and sustained investments across sectors to drive inclusive and long-term economic development in Haryana. Policy recommendations include prioritizing growth-driving sectors, enhancing human capital through increased spending on education and health, and ensuring balanced allocation to address structural inefficiencies.